Energy, Urbanization, and Sustainability Indicators: Empirical Data from Kazakhstan - Tleppayev, Arsen; Zeinolla, Saule; Abishova, Saltanat; Baibussinova, Gulden (International Journal of Energy Economics and Policy, 2023)
This paper intends to examine the connections between Kazakhstan's environmental indicators (CO2 emissions and solid waste), urbanization, economic development, and energy consumption. Time-series data for the years 1992 to 2020 were used in the paper; the data were derived from World Development Indicators found in the World Bank database. The methodology of this paper implements the Vector Error Correction Model based on the Granger causality Test. The empirical findings show that there is evidence that, in the near term, both urbanization and energy consumption contribute to CO2 emissions in Kazakhstan and in addition, the results demonstrate that urbanization contribute to energy consumption. Therefore, policies are required to reduce the effects of urbanization by boosting public instruments to preserve environmental quality and use more energy in sustainable manner. In addition, regulations for energy conservation are required across all industries, but particularly in the transportation and energy sector. These policies must also promote and maximize the use of alternative energy sources.